A new species of Phycodes from China (Lepidoptera: Sesioidea: Brachodidae) - Kallies, Axel; Wang, Min; Arita, Yutaka (Zootaxa, 2011)
Brachodidae are a small family of fewer than 140 described species that are distributed worldwide except in North America. They reach their greatest diversity in the tropical regions of Asia and South America; however, many species occur in the Palaearctic region and in Australia, but these are restricted to a small number of genera. More than 40 species are known from the Oriental region and many more await description (Kallies 1998, 2000, 2004).